STRATEGI PENGEMBANGAN USAHA ABON DAGING SAPI PADA INDUSTRI âCITRA LESTARI PRODUCTIONâDI KOTA PALU - Putri, Trimiranti; Lamusa, Arifuddin (AGROTEKBIS, 2017)
Abon are foods made from meat that has been shredded or separated fiber, then add seasonings and fried. The purpose of the SME "Citra Lestari Production" in the city of Palu. This study determined the location of a deliberate, determine the respondents in this study is done intentionally (purposive), management and employees as respondents. The result of the calculation of the value of the rating and weighting factors external business development strategies abon SMEs "Citra Lestari Production" obtained by subtraction between multiple opportunities (Opportunities) and threats (Threaths) That the Y axis in the diagram SWOT is 1.19, while the results of the calculation SMEs "Bieber Production" obtained from the reduction of the power factor (strengths) and weakness (weakness) is 2.36 to 1.04 = 1.32 is used as the horizontal axis atausumbu X, X in the diagram SWOT makasumbu was 1.32 position the business for its growth strategy abon SMEs "Citra Lestari Production" is in quadrant I, which in this position a business or industry has a strong position and a chance to develop. SWOT quadrant of the result of the implementation of strategies for SMEs "Citra Lestari Production" that is SO strategy. SO strategy is a strategy that can be used for business / industry has strengths and opportunities that can benefit opportunities.Â Key Words: Enterprise Development strategy, Shredded beef "Citra Lestari Production" .